Pengaruh Reputasi Merek Terhadap Kinerja Merek (Studi Kasus Pada Air Minum Dalam Kemasan) - Bayu Hasti; Lingga Yuliana (LPPM Institut Pendidikan Nusantara Global, 2026)
The purpose of this study is to examine the influence of brand reputation on brand performance with a case study of the AQUA brand. This study contributes to the development of literature in the field of brand management, particularly focusing on the relationship between brand reputation and brand performance in the context of Bottled Drinking Water. This study uses a quantitative descriptive method with a purposive sampling technique. Respondents involved in this study are customers who use the AQUA brand. The data used are primary data obtained through a questionnaire created with Google Form with a total of 124 respondents in the Greater Jakarta area. The data analysis technique uses Partial Least Square with the SmartPLS analysis tool version 4.1.0.0. The results of the study indicate that Brand Reputation has a positive and significant influence on Brand Performance. This study provides practical directions for AQUA brand managers to place reputation as the main focus of marketing and operational strategies. Efforts to strengthen reputation need to be carried out through various approaches such as product quality consistency, transparent marketing communications, consumer involvement in sustainability programs, and rapid responses to public issues. Strengthening reputation can also be achieved through a value-based differentiation strategy, so that AQUA is perceived not only as a consumer product but as a brand that prioritizes health, environmental sustainability, and social responsibility.